Microsatellite markers associated with genes expressed in developing wings of Bicyclus anynana butterflies - Beldade, P. (2009)
Deriving useful microsatellite markers in lepidopterans has been challenging when relying on scans of genomic DNA libraries, presumably due to repetitiveness in their genomes. We assayed 96 of 320 microsatellites identified in silico from a collection of Bicyclus anynana ESTs, in 11 independent individuals from a laboratory population.From the 68 successful assays, we identified 40 polymorphic markers including 22 with BLAST-based annotation. Nine of 12 selected polymorphic markers tested in a panel of 24 wild-caught individuals converted to successful assays and were all polymorphic. We discuss how microsatellite discovery in ESTs is an efficient strategy with important attendant advantages.